2017
DOI: 10.1038/s41397-017-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BCL2L11 polymorphism on osteonecrosis during treatment of childhood acute lymphoblastic leukemia

Abstract: Osteonecrosis (ON) is corticosteroid-related complication, reported in children with acute lymphoblastic leukemia (ALL). We have previously found that polymorphisms in BCL2L11 gene coding for pro-apoptotic Bim protein influence reduction of overall survival (OS) in a corticosteroid (CS) dose-dependent manner in childhood ALL patients. The same set of SNPs was here investigated for an association with CS-related ON assessed retrospectively in 304 children with ALL from Quebec (QcALL cohort) who received Dana-Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Padhye et al, ( 2016 ) and Sakamoto et al, ( 2018 ) reported that the incidence of ON is 7% among their study population. Moreover, Mattano et al, ( 2000 ), Plesa et al, ( 2019 ), and Pui et al, ( 2009 ), reported that the prevalence of ON among their patients was 9.3%, 10.5%, and 12%, respectively. The published prevalence of ON in children with ALL varies widely depending on the definition of ON, treatment protocol, and selection of patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Padhye et al, ( 2016 ) and Sakamoto et al, ( 2018 ) reported that the incidence of ON is 7% among their study population. Moreover, Mattano et al, ( 2000 ), Plesa et al, ( 2019 ), and Pui et al, ( 2009 ), reported that the prevalence of ON among their patients was 9.3%, 10.5%, and 12%, respectively. The published prevalence of ON in children with ALL varies widely depending on the definition of ON, treatment protocol, and selection of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Another risk factor for ON is sex. Many studies reported higher risk of ON in girls than boys (Aricò et al, 2003; French et al, 2008; Högler et al, 2007; Plesa et al, 2019; Strauss et al, 2001; Te Winkel et al., 2011), which was found in our study although other studies have not confirmed this (Barr & Sala, 2008; Mory et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the 5-year CI of orthopedic events for patient subgroups. The majority of the 100 ON events documented occurred in the hip (48) with the remainder occurring in the knee (20) and other locations (32).…”
Section: Orthopedic Eventsmentioning
confidence: 99%
“…The 891T>G was also confirmed in a replication cohort and influenced in vitro Bim gamma isoform levels. Bim proteins are believed to be involved in the sensitivity of ALL cells to corticosteroid-induced apoptosis ( Plesa et al., 2019 ). A GWAS in children with ALL and osteonecrosis showed that the SNP rs10989692 near the glutamate receptor GRIN3A locus, was associated with osteonecrosis ( Karol et al., 2015 ).…”
Section: Role Of Pharmacogenetic Variations In Chemotherapeutic Relatmentioning
confidence: 99%